Estudio de prefactibilidad para la instalación de una planta procesadora de malta para la producción de cerveza artesanal - Bellido Ayala, Gabriela Rosmery (2021)
The objective of the project is to determine the commercial, technical, economic, financial and social viability of the installation of a malt production plant aim to the production of craft beer. The product to be produced is base malt in polypropylene bags of 25kg, which has a market demand of 950 274,50 kg for the last year estimated of the project. The price of this product is S/ 4,15 per kg of base malt. The production plant will be located in Lurigancho district which will have an area of 622 m2. The size of this production plant will be 102,63 kg/h, determined by the technology. The production process of base malt contemplate the following steps: cleaning, steeping, germination, kilning, cooling, deculming and bagging. The total investment required for the project is S/ 3 617 617,55. Considering this amount, 46,39% of it will be financed by the shareholders while the 53,61% left will be financed by a bank at a 5,94% interest rate. The project, evaluated by a cost of capital of 11,09%, presents an economic result of a S/ 78 076,81 NPV and a 11,71% IRR; as for the financial evaluation, the results present a S/ 456 847,36 NPV and a 17,70% IRR. Both evaluations conclude the viability and profitability of the project.